Music Therapy as a Nonpharmacological Intervention for Anxiety in Patients with a Thought Disorder. (4th March 2017) - Pavlov, Allison; Kameg, Kirstyn; Cline, Tom W.; Chiapetta, Laurel; Stark, Stacy; Mitchell, Ann M.
ABSTRACT: Music therapy has been identified as a non-pharmacological adjunct therapy to treat anxiety. This QI project aimed to assess the effects of music therapy on anxiety in a sample of patients hospitalized with a thought disorder. Participants were assessed pre- and post-group using a visual analog scale for anxiety. The intervention significantly reduced VAS scores from 3.1 pre-intervention to .897 immediately post-intervention ( p = 0.008). This data suggests that music therapy may be beneficial in the short term for this population and is a low risk intervention that provides positive outcomes without the risks associated with medications, seclusion, and restraint.